PENGARUH PENAMBAHAN ABU SEKAM DAN SERBUK KACA TERHADAP KUAT TEKAN DAN BERAT JENIS BETON - Ni Komang Ayu Agustini; Putu Aryastana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
Concrete production is identical to environmentally destructive starting from the process of stone blasting, burning process and carbon emissions in the air. The production of cement was declared as the world's second largest contributor of 7% of carbon emissions in the world after the power plant is therefore needed innovation of environmentally friendly concrete for the sustainability of infrastructure development without damaging the environment. Glass powder and ash husk can be used as partial substitution of cement as an alternative solution environmental problems. Both materials are expected to function as filler because it has potential as pozzolan materials. This study was conducted on the compressive strength and the properties of normal concrete materials against the effect of using husk ash and glass powder on concrete mixture at the Laboratory of Civil Engineering Department of Warmadewa University. The test was performed on 7 days concrete with variation of the addition of husk ash and glass powder by 5%, 10%, 15%, 20% and 25% by weight of cement Replacement of husk ash and glass powder to the weight of cement affects the compressive strength and specific gravity of the concrete. The strength of concrete with glass powder showed to have a higher compressive strength when compared to the compressive strength of husk ash ash. The maximum strength of concrete with glass powder is obtained at 10% when the maximum strength of concrete with the husk ash was added of 5%. In addition, on the specific gravity of concrete obtained the optimum value when the addition of glass powder and concrete respectively by 20% and 5%. Keyword: husk ash, glass powder, specific grafity of concrete, compressive strength of concrete